DAMPAK MUSLIM FRIENDLY TOURISM DAN HALAL FOOD TERHADAP KEBERLANJUTAN WISATA HALAL - Anggraini, Mila (MUTLAQAH: Jurnal Kajian Ekonomi Syariah, 2025)
This study aims to analyze the impact of Muslim Friendly Tourism and Halal Food on the sustainability of halal tourism in Medan Barat District, a region striving to strengthen its position as a Muslim-friendly destination amid increasing global competition in halal tourism. The research employed a quantitative approach using multiple linear regression analysis through SPSS software. Data were collected through questionnaires distributed to 96 respondents, consisting of Muslim tourists and tourism stakeholders in the region. The results show that Muslim Friendly Tourism (X1) significantly influences halal tourism sustainability (Y), indicated by a t-value of 4.777 > 1.985 and a significance value of 0.000 < 0.05. Similarly, Halal Food (X2) has a significant effect with a t-value of 3.355 and a significance level of 0.001. The coefficient of determination (R²) is 0.774, meaning 77.4% of halal tourism sustainability is explained by both variables. These findings imply that strengthening Muslim-friendly facilities and halal food availability is essential to ensure the long-term competitiveness and sustainability of halal tourism destinations.